Gastrointestinal polyps in McCune Albright syndrome. Issue 7 (28th February 2011) - Zacharin, Margaret; Bajpai, Anurag; Chow, Chung Wo; Catto-Smith, Anthony; Stratakis, Constantine; Wong, Michelle W; Scott, Rodney
Abstract : Background: McCune Albright syndrome (MAS), a disorder caused by somatic activating mutations in the GNAS gene, usually presents with cutaneous, skeletal, and endocrine manifestations. While focal lesions involving multiple tissues have been identified in MAS, almost nothing is known about gastrointestinal lesions in this disease. Methods: Two MAS patients with perioral freckling, resembling Peutz–Jeghers syndrome (PJS), and two MAS patients without similar pigmentation underwent gastrointestinal endoscopy to establish if they had coexisting hamartomatous polyposis. Three of 4 subjects had documented GNAS mutations in peripheral blood. Genetic testing for STK11 and PRKAR1A genes was performed to exclude presence of coexistent PJS and Carney complex. Genetic testing of biopsy material was also performed. Results: Hamartomatous gastrointestinal polyps with histological features similar to those in PJS were observed in all 4 subjects, only in the stomach and/or upper duodenum. Activating GNAS mutations were found in the polyps or adjacent mucosa in 3 of 4 subjects. One patient each had mutation only in the blood or tissue, while 2 patients had both. No subject harboured any detectable PRKARIA or STK11 mutation as determined by direct DNA sequencing and copy number variation analysis. Conclusions: These findings confirm that gastrointestinal polyps are a common manifestation of MAS, indicate an overlap between MAS and PJS, and point towards a putative interaction between the GNAS and STK11 genes in the pathogenesis of these two disorders. The findings suggest a need for routine gastrointestinal endoscopy in patients with MAS, to establish the true incidence of polyps in these patients.